Development Of Picture Storybooks Based On Sasak Tribe Local Wisdom For Third Grade Students - Saadatul Adawiah; Sukri, Sukri; Ilham Handika (Insights: Journal of Primary Education Research, 2025)
The globalization era and rapid technological development threaten Indonesian local wisdom preservation, particularly oral traditions. Globalization triggers shifts toward more practical modern lifestyles, exacerbated by insufficient younger generations interested in inheriting their culture. The objective of this study is to create an illustrated narrative book incorporating indigenous Sasak cultural knowledge intended for elementary third-year learners at SDN 44 Cakranegara. Pre-research interviews and questionnaires revealed urgency: (1) students did not know Tetuntel Tuntel dait Tegodek Godek, a distinctive Sasak folktale; (2) limited picture storybooks about local wisdom. Analysis of student textbook theme 2 “Loving Plants and Animals” showed: folktales presented only as text without attractive visuals, overly simplistic content lacking regional distinctiveness, and no introduction to Indonesian archipelago folktales. This condition created local cultural introduction gaps and disrupted intergenerational cultural transmission. R&D method using ADDIE model was selected for its systematic and structured framework producing quality learning products. Analysis: identifying students' knowledge gaps. Design: designing bilingual book concepts. Development: producing books with Sasak-Indonesian texts, engaging illustrations, and local wisdom values. Implementation: pilot testing with target users. Evaluation: expert validation and user response measurement. Validation results were excellent: media expert 85.71%, material expert 92.31%, student response 98.53%, teacher response 95%. The book effectively facilitates folktale comprehension and introduces Sasak local wisdom, contributing to local cultural preservation.